2020
DOI: 10.24321/2455.9318.202015
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Musculoskeletal Dysfunctions on Quality of Life of Pregnant Women

Abstract: Background: Pregnancy is a special condition which is neither a disease nor a normal body status. The anatomical, physiological, and biochemical adjustments are significant during pregnancy, starting soon after fertilization and continuing throughout pregnancy. Reasons for pain during pregnancy include hormonal changes, increased weight, postural variations and impaired strength and co-ordination of abdominal and pelvic muscles. Musculoskeletal pain during pregnancy can have a significant negative impact on da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…In addition, stated that muscle cramps in the leg muscles are complaints that are often felt generally in women compared to men 13 . Another study stated that complaints such as low back pain occurred approximately 60% and muscle cramps 42% were the most common complaints experienced by pregnant women 14 . In another study showed that as many as 334 pregnant women who were the research sample experienced muscle cramps during pregnancy 15 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, stated that muscle cramps in the leg muscles are complaints that are often felt generally in women compared to men 13 . Another study stated that complaints such as low back pain occurred approximately 60% and muscle cramps 42% were the most common complaints experienced by pregnant women 14 . In another study showed that as many as 334 pregnant women who were the research sample experienced muscle cramps during pregnancy 15 .…”
Section: Discussionmentioning
confidence: 99%